The Power of a Profound Experience With Nature: Living With Meaning - Mathers, Becky; Brymer, Eric (Frontiers in Psychology, 2022)
Nature based experiences have been linked to significant positive outcomes for people and the planet. Significant life experience research investigates the associations between formative experiences in nature and resulting environmental concern and action, including both singular events and repeated experiences. However, little is known about the long-term impacts of singular profound experiences with nature. This research sought to better understand how a singular, meaningful experience defines an individual’s self-awareness of his or her relationship with nature, changes social relationships, and directs environmental decisions and behaviors. Twenty-one adults who had a profound experience with nature participated in a semi-structured interview exploring how they make sense of their experience, the meaning they attribute to it, and the role it served in their lives. Three themes resulted from the thematic analysis process: (1) Living in relation with nature, (2) Living authentically, and (3) Living a meaningful life. The findings demonstrate that a single profound experience with nature can have long-lasting and significant effects on an individual. Understanding these long-term influences of a profound experience with nature have implications for intervention designers such as health practitioners and environmental educators, as well as policy-makers.